Septicemic Infection Suspect In Jenkins' Whipray Pateobatis jenkinsii (Annandale, 1909): A Case Report - Rifky Rizkiantino; Ridzki M.F. Binol (Jurnal Sain Veteriner, 2020)
A wild-captive male Jenkins' whipray was found dead in a quarantine tank with a clinical sign before death in the form of decreased appetite for a week. The treatment history was oral administration of enrofloxacin antibiotic tablets. The therapy period lasts for ten days. The last treatment was the administration of Hepavit® (liver extract) and intramuscular injection of enrofloxacin antibiotic. One day before the death, blood was collected and then examined for the hematocrit and some parameters of chemical blood. The results of blood examination were found a decrease in blood urea nitrogen (BUN), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) levels, increased glucose level, decreased total protein and albumin levels, and increased globulin level. Anatomical pathology examination was found lesions on the tail, around the eyes, and claspers. Hemorrhagic lesions were found in the mucous layer of the esophagus, stomach, and spiral colon. The blood clot was found under the tunica layer of testicular organs. The liver is damaged by showing a non-homogeneous coloration, organ thickening, congestion, and fragile consistency. Based on the results of the blood examination and was supported by the results of the anatomical pathology examination after death, it is suspected that the fish died due to the condition of septicemia infection during the previous few weeks.